2008
DOI: 10.1128/aem.02512-07
|View full text |Cite
|
Sign up to set email alerts
|

A Legionella pneumophila Peptidyl-Prolyl cis - trans Isomerase Present in Culture Supernatants Is Necessary for Optimal Growth at Low Temperatures

Abstract: Several Legionella pneumophila proteins were highly expressed in low-temperature supernatants. One of these proteins was the peptidyl-prolyl isomerase PpiB. Mutants lacking ppiB exhibited reduced growth at 17°C. Since PpiB lacked a signal sequence and was present in 17°C supernatants of type II and type IV secretion mutants, this protein may be secreted by a novel mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 44 publications
1
44
0
2
Order By: Relevance
“…For example, when 130b is grown in BYE broth at 37°C, the secretome encompasses more than 25 proteins, including many degradative enzymes as well as proteins with no similarity to known proteins (2-4, 6, 10, 11, 19, 20, 23, 31, 49-51). Also, 2D polyacrylamide gel electrophoresis analysis of supernatants produced during growth at 12 to 17°C revealed other exoproteins that are more pronounced at low temperatures (55). Although more work is needed to identify the critical secreted factors, the new data presented here significantly increase our appreciation for the role that type II secretion plays in Legionella ecology.…”
mentioning
confidence: 67%
“…For example, when 130b is grown in BYE broth at 37°C, the secretome encompasses more than 25 proteins, including many degradative enzymes as well as proteins with no similarity to known proteins (2-4, 6, 10, 11, 19, 20, 23, 31, 49-51). Also, 2D polyacrylamide gel electrophoresis analysis of supernatants produced during growth at 12 to 17°C revealed other exoproteins that are more pronounced at low temperatures (55). Although more work is needed to identify the critical secreted factors, the new data presented here significantly increase our appreciation for the role that type II secretion plays in Legionella ecology.…”
mentioning
confidence: 67%
“…The T2S mutants are not impaired for entry into the amoebae, indicating that T2S is promoting bacterial resistance to intracellular killing and/or facilitating replication itself (22). Others of our studies have shown that T2S also promotes the persistence of L. pneumophila in the environment by facilitating extracellular survival in low-temperature water samples (18,(22)(23)(24)(25). Furthermore, L. pneumophila T2S helps to mediate the secretion of a surfactant that confers both sliding motility and antibacterial activity (26,27).…”
mentioning
confidence: 87%
“…The Lsp system presumably secretes factors that aid L. pneumophila persistence at low temperatures, as the growth of lsp mutants was stimulated by the addition of culture supernatant from the wild-type strain (310). One of these factors is a secreted peptidyl-prolyl cis-trans isomerase present in the culture supernatant (308). Additional factors were recently identified from a transposon mutant screen for growth defects at low temperatures.…”
Section: The Lsp Type II Secretion Systemmentioning
confidence: 99%